Village Development: Transendental-Based Policy for Utilization of Natural Resources and Environment - Miftia Nur Annisa; Rika Maryani; Rina Arum Prastyanti (Universitas Muhammadiyah Surakarta, 2022)
This study aims to explore village development policies in the use of natural resources and the environment based on transcendental values, where the urgency of this research lies in the village development model by prioritizing the transcendental paradigm. This study uses a juridical - normative research method by reviewing Law No. 6 of 2014 concerning Villages which is harmonized with a philosophical approach. This study examines transcendental values as the basis for village development in utilizing natural resources and the environment, where previous studies were only oriented towards materialism in improving the economy of the community. The results of the study show that natural resources and the environment are gifts from God that must be able to be utilized for the benefit of the community. As a gift from God, natural resources and the environment in their use must always prioritize ethics and morals. Ethical and moral values are the essence of transcendence as well as capital in village development. While the results of the study concluded that the government's policy on village development through Law No. 6 of 2014 concerning Villages Article 81 (3), is very important to be carried out in order to be able to maintain natural resources and the environment that are beneficial to human life. The existence of transcendental values is able to preserve the ecosystem of natural resources and the environment for the development of villages in the archipelago. Ethical and moral values are the essence of transcendence as well as capital in village development. While the results of the study obtained a conclusion that government policy on village development through Law No. 6 of 2014 concerning Villages Article 81 (3), is very important to be carried out in order to be able to maintain natural resources and the environment that are beneficial to human life. The existence of transcendental values is able to preserve the ecosystem of natural resources and the environment for the development of villages in the archipelago. Ethical and moral values are the essence of transcendence as well as capital in village development. While the results of the study obtained a conclusion that government policy on village development through Law No. 6 of 2014 concerning Villages Article 81 (3), is very important to be carried out in order to be able to maintain natural resources and the environment that are beneficial to human life. The existence of transcendental values is able to preserve the ecosystem of natural resources and the environment for the development of villages in the archipelago. It is very important to run in order to be able to maintain natural resources and the environment that are beneficial to human life. The existence of transcendental values is able to preserve the ecosystem of natural resources and the environment for the development of villages in the archipelago. It is very important to run in order to be able to maintain natural resources and the environment that are beneficial to human life. The existence of transcendental values is able to preserve the ecosystem of natural resources and the environment for the development of villages in the archipelago.